PEDAGOGICAL CONDITIONS OF INDIVIDUALIZATIONS PROFESSIONALLY ORIENTED TRAINING FOREIGN LANGUAGES OF NON-LANGUAGE STUDENTS SPECIALTIES IN HIGHER PEDAGOGICAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the pedagogocal condition of individualization o f the professional oriented training o f students of non-inguistic specialities at higher educational establishments. The possibility of every student’s effective training has been given.